The factors affecting the workplace safety in manufacturing industry / Nur Shafini Mohd Said ... [et al.] - Mohd Said, Nur Shafini; Mohamad Yusoff, Nur Ayuni; Omar Ali, Siti Rapidah; Abdul Manaf, Suhaily Maizan; Adenan, Nur Dalila (Universiti Teknologi MARA, Perlis, 2020)
Lately, issues of incidents in workplace are increasing and this situation obviously brings bad impact to the management and also the workers in manufacturing industries. This quantitative study identifed the factors that influence the workplace safety among the workers. The researcher has selected workers from production department as the population for this study. To complete this study, the researcher has developed a set of questionnaire as the research instrument for collecting the data. The questionnaire consisted of two parts; Part A and Part B. Part A is the demographic factors while part B is the variables involve in this research. The variables were employee involvement, management commitment, workplace environment and workplace safety. The target population was 534 who are workers from production department only. The sampling method was a stratified random sampling based on the table of Krejcie and Morgan and the sample size was 217. The findings were assessed by using the Statistical Package for the Social Sciences (SPSS) version 23. SPSS then were analyzed the instrument throughout reliability analysis and correlation analysis. The study revealed that three independent variables contributed in influencing the workplace safety among the workers at Malaysian manufacturing sector. In addition, this study provides the management and workers with a few suggestions and opinions to reduce or eliminate the rate of workplace incidents